NOTE ON THE DISTRIBUTION OF BIVALVE SPATS IN VELLAR ESTUARY - Jayabal, R; Kalyani, M (Indian Journal of Fisheries, 2011)
Survey was carried out over a stretch of 9 km of the estuarine shore for knowing the seed resources of bivalves in Vellar estuary and their seasonal distributions. Sediment samples, each from a 25 cm^ area at half-metre depth, were collected at random between two consecutive stations. These samples were seived using a sieve of 0.5 mm mesh. Samples were then analysed in the laboratory and the bivalve spats were quantitatively estimated and identified up to species level. The spats at 3-5 nun size have the morphological characters of the adults. During the surveys salinity, dissolved-oxygen content and temperature were also estimated at each sampling station